(untitled) (Western European Journal of Medicine and Medical Science, 2024)
This study is devoted to the study of the clinical and experimental basis of the use of polylactic acid biomaterial for the restoration of bone deformities in the face-jaw area. The purpose of the research is to determine the effectiveness of bone defect restoration methods using modern biomaterials.